1994
DOI: 10.1111/j.1600-0587.1994.tb00102.x
|View full text |Cite
|
Sign up to set email alerts
|

Large plant size counteracts early seed predation during the extended flowering season of a Silene uniflora (Caryophyllaceae) population

Abstract: A population of the alvar race of the perennial herb, Silene uniflora (Caryophyllaceae), which grows on thin soils in open alvar habitats on the Baltic island of Oland SE Sweden, was found to have an extended and more or less bimodal flowering phenology Large individuals produced flowers during both periods, while small, and presumably young, individuals only produced flowers in either of the two periods, or in part of both In the early flowering period plants were heavily infested by the seed‐predatory larvae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

1996
1996
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 30 publications
1
23
0
2
Order By: Relevance
“…Most field surveys compare temporal variation in the intensity of seed and flower predation and flowering phenology to infer the direction of selection acting on phenology. Most studies found that flowering off-peak (either early [23,[34][35][36][37], or late [11,[38][39][40][41]) is associated with reduced seed predation, probably because fewer herbivores are present at those times. Similar effects are highlighted by studies indicating highest seed predation during peak flowering [42][43][44], especially when peak flowering attracts more seed predators owing to a higher density of flowers and fruits ( [28], J.A.…”
Section: Interactions With Mutualists: Pollinatorsmentioning
confidence: 99%
“…Most field surveys compare temporal variation in the intensity of seed and flower predation and flowering phenology to infer the direction of selection acting on phenology. Most studies found that flowering off-peak (either early [23,[34][35][36][37], or late [11,[38][39][40][41]) is associated with reduced seed predation, probably because fewer herbivores are present at those times. Similar effects are highlighted by studies indicating highest seed predation during peak flowering [42][43][44], especially when peak flowering attracts more seed predators owing to a higher density of flowers and fruits ( [28], J.A.…”
Section: Interactions With Mutualists: Pollinatorsmentioning
confidence: 99%
“…Several studies demonstrated a size-dependent variation in flowering phenology (Pettersson 1994;Ollerton and Lack 1998;Sandring et al 2007). Total flower number within inflorescences significantly correlated with the timing of first flowering in G. nipponica.…”
Section: Kawai and Kudo 14mentioning
confidence: 99%
“…In addition, predation by Hadena moths may remove the majority of the capsules produced by S. uniflora ssp. petraea during the early part of the flowering season (Pettersson 1994;H.C. Prentice, unpublished data).…”
Section: Barriers To Hybridization Between S Vulgaris and S Uniflormentioning
confidence: 99%